The Unequal Distribution of Linguistic Capital in a Transnational Economic Order - Rössel, Jörg; Schroedter, Julia H. (Frontiers in Sociology, 2021)
Foreign language proficiency is an unequally distributed form of linguistic capital that is becoming increasingly important in contemporary societies: first, it enables persons to participate transnationally in educational activities and in labour markets beyond the national institutions of their home country. It is also crucial for integrating an increasing share of the population with a migration background into the labour market. The well-established and empirically successful standard model for explaining differences in language proficiency is the economic approach to language. The main aim of this article is to enrich the discussion on language proficiency by deriving hypotheses from the sociological theory of reproduction and the discourse on migrant integration. Variables are included which have not been tested in a broad fashion in previous empirical research. We use data on different groups of migrants and non-migrants in multilingual Switzerland, where we could study the determinants of the unequal distribution of language proficiency in the four official languages and foreign language repertoire in general. Our main results show that the hypotheses derived from the two theoretical discussions are empirically supported overall and contribute substantially to the explanation of language proficiency. However, most of these variables indicate the importance of unequally distributed opportunities for learning languages, thus highlighting that language learning may be less of an investment driven by economic incentives such as higher earnings than part of the more general process of reproducing social inequality structures.